2003
DOI: 10.1139/t03-009
|View full text |Cite
|
Sign up to set email alerts
|

Nγfor rough strip footing using the method of characteristics

Abstract: By using the method of characteristics, the bearing capacity factor Nγ was computed for a rough strip footing. The analysis was performed by considering a curved nonplastic wedge under the foundation base bounded by curved slip lines being tangential to the base of the footing at its either edge and inclined at an angle π/4 - ϕ/2 with the vertical axis of symmetry. The existing theories in the literature for rough footings, which usually employ a triangular wedge below the footing base, were generally found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(39 citation statements)
references
References 16 publications
4
30
5
Order By: Relevance
“…For N q , the values from the present simulation are a little smaller than those obtained from Refs. [3,18]. For N γ , when ϕ = 5 • , the values from the present analysis are larger than those from Refs.…”
Section: Analysis and Discussion Of Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…For N q , the values from the present simulation are a little smaller than those obtained from Refs. [3,18]. For N γ , when ϕ = 5 • , the values from the present analysis are larger than those from Refs.…”
Section: Analysis and Discussion Of Resultscontrasting
confidence: 80%
“…Bolton et al [3,14,16] determined the factors N c for frictional and frictionless material and Cox [17] determined the factors N γ for smooth footings by means of the method of characteristics. Kumar et al [18] determined the value of N γ for a circular rough footing by using the method of characteristics with an associative flow rule. Although the researchers have already found that the nonassociativity of soil had an important influence on the bearing capacity of footings, it is noted that the variation of both friction angle ϕ and dilation angle ψ in these studies are limited to a small range of nonassociativity.…”
Section: Introductionmentioning
confidence: 99%
“…In order to arrive at the vertical pressure ( p) along the footing base (CE) above the trapped wedge, similar to the previous analysis of the author [22], it was assumed that for any element efgh, within trapped wedge as shown in Figure 2, the resultant of the shear forces along the vertical planes eh and fg does not have any contribution in the vertical direction.…”
Section: Determination Of the Failure Loadmentioning
confidence: 99%
“…Finding accurate prediction for the bearing capacity of strip footings is one of the fundamental problems in geotechnical engineering and, several researches are devoted to the subject [1]- [3]. An appealing choice to solve such problems is the application of numerical limit analysis (NLA).…”
Section: Introductionmentioning
confidence: 99%